PRACTICE GUIDELINES FOR THE USE OF STANDARDS FOR DESIGN OF INTERACTIVE SYSTEMS IN TERMAL IMAGING PROCESSING TASKS - A. Y. Tsunikov (Российский технологический журнал)
The article analyzes the critical quality parameters firmware optoelectronic systems (IPS) to meet the ergonomic requirements for work with computer systems: ISO 9241 - Ergonomics of human-machine interaction; ISO 10075 - Ergonomic principles related to mental workload when dealing with interactive systems; ISO 14915 - Ergonomics software multimedia user interfaces. According to the results of theoretical analysis of the current state of the problem of data processing automation of noisy and distorted IR images revealed that the image processing procedure is an indispensable component of the total signal processing procedure in the chain of data transformations from its registration photodetectors to the presentation to the operator, so the lack of standardized quantitative criterion imaging quality to solve practical problems of modern optoelectronic instrument makes it especially urgent to develop treatment algorithms thermal images with ergonomic requirements for computer systems. Practical recommendations are done to improve the reliability of the interpretation of the information provider, and thus improve the reliability of the situation prediction efficiency and APC information system as a whole.